Implementation of the Independent Entrepreneurship Program in Developing Students' Interests in Becoming Social Entrepreneurs - Septianing Pratiwi, Anisa; Ika Rizqi Meilya; Ratna Sari Dewi (Journal of Nonformal Education and Community Empowerment, 2024)
The aim of this study was to describe the implementation of the independent entrepreneurship program in developing students' interest in entrepreneurship. Describe students' interest in becoming social entrepreneurs after participating in the 2023 UNY independent entrepreneurship program. Describe the supporting and inhibiting factors in students' interest in becoming social entrepreneurs. This research method uses a qualitative approach. The subjects in this study were the head of the organizers, supervisors, and 5 student participants in the program. The results of this study indicate the implementation of the 2023 UNY independent entrepreneurship program in developing students' interest in entrepreneurship was carried out very well, starting from the 3 stages of learning in the independent entrepreneurship program as indicators that influence students' interest in entrepreneurship. Students' interest in becoming social entrepreneurs shows a positive direction, based on students' experiences in participating in the entire series of independent entrepreneurship program activities. Supporting factors in students' interest in becoming social entrepreneurs are self-motivation, ability, feelings of happiness, and family support. Meanwhile, the inhibiting factor in students' interest in becoming social entrepreneurs is the community environment. This study provides a new contribution in understanding the role of the independent entrepreneurship program in shaping students' interest in social entrepreneurship. This study specifically explores the impact of participation experiences in the program on students' motivation and orientation towards social entrepreneurship, which has rarely been studied before. In addition, this study identifies unique supporting and inhibiting factors in the context of implementing entrepreneurship programs in higher education, especially in Indonesia.